Improvement of life insurance-related accounting opera-tions within the New Economy - DOBRIN, Marinică (Annals of Spiru Haret University. Economic Series, 2010)
This paper outlines the life insurance-related accounting operations, in consideration to the harmonization of the Romanian legislation with the International Financial Reporting Standards. The main accounting operations specific to the life insurance sector include: accounting of revenues and expenses derived from life insurance operations (recording the premiums written, recording the payment of insurance premiums, termination of insurance policy, recording the compensation expenses), accounting of operations related to the setting up and using the technical reserves for life insurance (general principles, accounting of premium reserves, accounting of loss reserve, accounting of the reserve for benefits and discounts, accounting of mathematical reserve, accounting of other life insurance-related technical reserves).